Level V Clearance in Neck Dissection for Papillary Thyroid Carcinoma: A Need for Homogeneous Studies - Battoo,Azhar Jan (2018)
Abstract Introduction Papillary thyroid carcinoma has a very high rate of lateral neck node metastases, and there is almost unanimity concerning the fact that some sort of formal neck dissection must be performed to address the clinical neck disease in these cases. Although there is an agreement that levels II to IV need to be cleared in these patients, the clearance of level V is debatable. Objectives We herein have tried to analyze various papers that have documented a structured approach to neck dissection in these patients. Moreover, we have also tried to consider this issue through various aspects, like spinal accessory nerve injury and the impact of neck recurrence on survival. Data Synthesis The PubMed, Medline, Google Scholar, Surveillance, Epidemiology, and End Results (SEER), and Ovid databases were searched for studies written in English that focused on lateral neck dissection (levels II–IV or II–V) for papillary thyroid carcinoma. Case reports with 10 patients or less were excluded. Conclusions The current evidence is equivocal whether to clear level V or not, and the studies published on this issue are very heterogeneous. Level II-IV versus level II-V selective neck dissections in node-positive papillary thyroid carcinoma patients is far from categorical, with pros and cons for both approaches. Hence, we feel that there is a need for more robust homogeneous data in order to provide an answer to this question.